2020
DOI: 10.18632/oncotarget.27640
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of lenvatinib for patients with unresectable hepatocellular carcinoma including after treatment with sorafenib: Real-world evidence and in vitro assessment via protein phosphorylation array

Abstract: The efficacy and safety of lenvatinib (LEN) as a second/third-line treatment for unresectable hepatocellular carcinoma (HCC) after sorafenib (SOR) therapy remains unknown. We evaluated the outcomes of second/third-line LEN treatment, investigated the sensitivity of a SOR-resistant HCC cell line (PLC/PRF5-R2) to LEN, and assessed their signal transduction pathways by protein array analysis. We retrospectively enrolled 57 patients with unresectable HCC. Fifty-three radiologically evaluated patients comprised 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…However, the most favorable MTA therapy for secondary treatment remains unclear as no head‐to‐head comparisons have been conducted among the MTAs. Moreover, the effectiveness of treatment with LEN after progression following SOR treatment has been reported in retrospective studies 8,9 . In contrast, the therapeutic efficacy and safety of SOR or RAM after disease progression following LEN treatment has been reported in small cohort studies 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the most favorable MTA therapy for secondary treatment remains unclear as no head‐to‐head comparisons have been conducted among the MTAs. Moreover, the effectiveness of treatment with LEN after progression following SOR treatment has been reported in retrospective studies 8,9 . In contrast, the therapeutic efficacy and safety of SOR or RAM after disease progression following LEN treatment has been reported in small cohort studies 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…These results reiterate the observation that better hepatic reserve function is associated with the therapeutic effect of LEN. [ 8 10 ] It has also been reported that the relative dose intensity (RDI) plays an important role in the therapeutic effect of LEN. [ 8 , 11 , 12 ] In all of our cases, hepatic reserve function was good and the RDI, up to the first imaging evaluation, was high (Case 1: 75%, Case 2: 100%, Case 3: 100%) (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 10 ] It has also been reported that the relative dose intensity (RDI) plays an important role in the therapeutic effect of LEN. [ 8 , 11 , 12 ] In all of our cases, hepatic reserve function was good and the RDI, up to the first imaging evaluation, was high (Case 1: 75%, Case 2: 100%, Case 3: 100%) (Table 1 ). Although in BCLC stage B, cTACE/TAE is a standard treatment for unresectable HCC, Arizumi et al and Ogasawara et al reported that the switch from cTACE to SOR significantly improved the OS in patients with intermediate-stage HCC who were refractory to cTACE therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a possibility that SOR can be used as a therapeutic agent after progression on treatment with LEN. In fact, we have reported that LEN treatment is moderately effective as the second‐line treatment after progression on SOR 14 …”
Section: Introductionmentioning
confidence: 99%
“…In fact, we have reported that LEN treatment is moderately effective as the second-line treatment after progression on SOR. 14 Therefore, in this study, we aimed to investigate the therapeutic effect and safety of SOR in patients with u-HCC after progression on treatment with LEN.…”
Section: Introductionmentioning
confidence: 99%